Effects of Morinda citrifolia L. fruit extract on diabetic retinopathy biomarkers in retinal cells in vitro - Hassan, Nisreen Dheyab (2018)
Diabetic retinopathy is a leading cause of vision loss. It has been correlated with increased oxidative stress and the activity of aldose reductase (AR). The aim of the present study was to evaluate the protective and therapeutic properties of Morinda citrifolia L. (known as noni) fruit extract, in human retinal pigment epithelial cells (ARPE-19) exposed to high glucose. ARPE-19 cell line was incubated in normal (5.5 mM) and high (45 mM) glucose for 5 days in the absence and presence of indicated doses of noni fruit extract (10 and 50 μg/ml). In another experiment ARPE-19 cell line was incubated in normal (5.5 mM) and high (45 mM) glucose for 4 days and then incubated with or without indicated doses of noni fruit extract (10 and 50 μg/ml) for 24 hours before termination of experiment. Cell viability was assessed by MTT assay. Aldose reducatase (AR), vascular endothelial growth factor (VEGF), and advanced glycation end products (AGEs) were determined by enzyme immunoassay (ELISA). Total glutathione (GSH), reactive oxygen species (ROS), and malondialdehyde (MDA) were also assessed. The results showed that GSH content was significantly decreased after the addition of high glucose concentration. The presence of noni fruit extract prevented the reduction and maintained the GSH at the level found in cells exposed to 5.5 mM glucose concentration. Moreover, the levels of ROS, AGEs and MDA were significantly increased (P<0.05) after high glucose exposure compared to cell exposed to 5.5 mM glucose. The presence of noni fruit extract had reduced and maintained the ROS, AGEs and MDA at the levels found in control cells. Notably, the high glucose condition led to a significantly increased of AR and VEGF as compared to control cells, and noni fruit extract prevented this increment. This study demonstrated that noni fruit extract could prevent high glucose–induced oxidative stress and VEGF secretion via inhibition of aldose reductase in human retinal pigment epithelial cells (ARPE-19). In addition, the results of this study indicated that noni fruit could be an ideal agent used for treatment and protection against biomarkers of diabetic retinopathy.